2017
DOI: 10.1108/k-12-2016-0348
|View full text |Cite
|
Sign up to set email alerts
|

Identifying high-value airlines customers for strategies of online marketing systems

Abstract: Purpose The purpose of this study is to discover valuable customers for enterprises. The international market of Taiwan airlines can be enhanced; thus, this study aims at Taiwan’s airline market as a research area. Design/methodology/approach This research uses data mining technologies with a proposed model to analyse airline customer values for big data online marketing systems, such as customer relationship management (CRM) system. The research applied supervised apriori algorithm, socio-economic variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The study outcomes identified two papers referring to aviation, both written by Chiang (2018Chiang ( , 2019. The author investigated Big Data use in CRM strategies in airports.…”
Section: Mapping Of Papers According To Research Areasmentioning
confidence: 99%
“…The study outcomes identified two papers referring to aviation, both written by Chiang (2018Chiang ( , 2019. The author investigated Big Data use in CRM strategies in airports.…”
Section: Mapping Of Papers According To Research Areasmentioning
confidence: 99%
“…Although RFM does not explicitly provide a net profit for customer value, Fader et al [11] indicated it can be used to build customer value. In addition, different industries can measure customer value from different view by using RFM's variants such as such as RFMDR [12], RFTM [13] and FSLC [14] in a more reasonable way. Meanwhile, RFM models show customer value in three-dimensional space or above, which makes it difficult for market decision makers to conduct marketing analysis.…”
Section: Customer Valuementioning
confidence: 99%
“…Marketing mechanism as a network of persons, users, providers and groups offers properties, services, skills, goods and ideas to meet customer demand based on collaboration (Choi and Joo, 2018; Kim and Kumar, 2018; Tsiakali, 2018). A marketing mechanism is a complicated group of multifaceted associations where market participants’ activities affect their companies, followers and customers in a long-term manner (Chiang, 2018; Ebrahimian et al , 2018). Also, it plays an increasingly noticeable part of economic action and theoretical study (Cluley and Greenhalf, 2018; Redmond, 2018).…”
Section: Introductionmentioning
confidence: 99%